2020
DOI: 10.1002/adfm.202000533
|View full text |Cite
|
Sign up to set email alerts
|

Excitons and Electron–Hole Liquid State in 2D γ‐Phase Group‐IV Monochalcogenides

Abstract: Different dispersion near the electronic band edge of a semiconductor can have great influence on its transport, thermoelectric, and optical properties. Using first-principles calculations, it is demonstrated that a new phase of group-IV monochalcogenides (γ-MX, M = Ge, Sn; X = S, Se, or Te) can be stabilized in monolayer limit. γ-MXs are shown to possess a unique band dispersion-that is, camel's back like structure-in the top valence band. The band nesting effect near the camel's back region induces a large e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 62 publications
10
70
0
Order By: Relevance
“…For example, the successive discoveries of integer 1,2 and fractional 3 quantum Hall effects and superconductivity have introduced new physics. Since the discovery of graphene, 4,5 the family of 2D materials has grown explosively, [6][7][8][9][10] including many famous members such as transition metal dichalcogenides, 11 hexagon boron nitride, 12 carbon boron nitride, 6,8 stanene, 9 etc. It is well known that strong fluctuations prohibit long-range magnetic order at finite temperature in a 2D system, as depicted by the Mermin-Wagner theorem.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the successive discoveries of integer 1,2 and fractional 3 quantum Hall effects and superconductivity have introduced new physics. Since the discovery of graphene, 4,5 the family of 2D materials has grown explosively, [6][7][8][9][10] including many famous members such as transition metal dichalcogenides, 11 hexagon boron nitride, 12 carbon boron nitride, 6,8 stanene, 9 etc. It is well known that strong fluctuations prohibit long-range magnetic order at finite temperature in a 2D system, as depicted by the Mermin-Wagner theorem.…”
Section: Introductionmentioning
confidence: 99%
“…1(a). Previous theoretical work [21] showed that this ABCA-sequence quadruple layer is stable and is energetically preferred to other stacking sequences such as ABAB, ABAC, and ABBA. For bulk γ-GeSe, one has to consider how quadruple layers are stacked, and it was reported that AB stacking of quadruple layers is energetically preferred to AA stacking [21].…”
Section: Resultsmentioning
confidence: 90%
“…Recently, a new atomic structure of group-IV monochalcogenide γ-MX having a double-layer honeycomb lattice (DLHL) has been predicted theoretically [21]. The predicted monolayer and AB-stacked bulk γ-GeSe are centrosymmetric, so the intrinsic ferroelectricity does not appear.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the successful of graphene [1,2], a great deal of research efforts are devoted toward the investigation of two-dimensional (2D) materials in last decade [3,4]. The 2D materials not only exhibit unique and fascinating physical features by comparing their bulk counterpart [5][6][7][8][9][10], but also support a new dimension to tune the properties of by engineering the interlayer coupling [11][12][13]. The linear dispersion at K point endows novel phenomena in monolayer graphene, including the ultra-high mobility, fantastic thermal and electronic conduction and the anomalous room-temperature quantum Hall effect.…”
Section: Introductionmentioning
confidence: 99%
“…The graphene-based devices have also been explored [5][6][7]. Transition from indirect to direct bandgap is revealed in transition-metal chalcogenides (TMCs) by reducing the thickness to monolayer [8][9][10]. Moreover, a large number of new 2D materials have been theoretically designed and experimentally realized, like monoelemental materials (silicene, germanene, phosphorene, borophene), MXenes, organic materials and nitrides.…”
Section: Introductionmentioning
confidence: 99%